Techno-economic assessment of coal- or biomass-fired oxy-combustion power plants with supercritical carbon dioxide cycle - Wei, Xiaoyu; Manovic, Vasilije; Hanak, Dawid P. (Elsevier, 2020)
Oxy-fuel combustion is regarded as a feasible technology that can contribute towards decarbonisation of the power industry. Although it has been shown that oxy-fuel combustion results in lower carbon dioxide emissions at a lower cost of carbon dioxide captured compared to the mature amine scrubbing process, its implementation still results in high economic penalties. This study proposes to replace the conventional steam cycle in the state-of-the-art oxy-combustion coal-fired power plants with the supercritical carbon dioxide cycle to reduce both economic and efficiency penalties. In addition, in order to further reduce carbon dioxide emissions, biomass is considered as a replacement fuel for coal in the oxy-fuel combustion power plant and the proposed process becomes a type of bio-energy with carbon capture and storage. The process models were developed in Aspen Plus™ to assess techno-economic feasibility of the considered processes. The results showed that on replacement of the conventional steam cycle with the supercritical carbon dioxide cycle, the efficiency penalties were reduced by up to 2% points and the levelised cost of electricity was reduced up to 4.6% (4.1 €/MWh). Moreover, when biomass was used as a fuel, the net efficiency penalties increased by 0.5% points and the levelised cost of electricity increased by 24.4 €/MWh. Although techno-economic performance in this case was less favourable under no carbon tax conditions, using biomass resulted in significant negative carbon dioxide emissions (-3.70 megatonnes of carbon dioxide per annum). Such negative emissions can offset carbon dioxide emissions from other sources that are relatively difficult to decarbonise. If the carbon tax is above 24 € per tonne of carbon dioxide, bio-energy with carbon capture and storage became more economically feasible than fossil fuel with carbon capture and storage
Keywords: feasibility assessment; techno-economic assessment; process modelling; bio-energy and carbon capture and storage; supercritical carbon dioxide Brayton cycle; oxy-fuel combustion